Effect of preoperative immunonutrition and other nutrition models on cellular immune parameters - (:unkn) unknown (W J G PRESS, 2009)
AIM: To evaluate the effects of preoperative immunonutrition and other nutrition models on the cellular immunity parameters of patients with gastrointestinal tumors before surgical intervention. In addition, effects on postoperative complications were examined. METHODS: Patients with gastrointestinal tumors were randomized into 3 groups. The immunonutrition group received a combination of arginine, fatty acids and nucleotides. The second and third group received normal nutrition and standard enteral nutrition, respectively. Nutrition protocols were administered for 7 d prior to the operation. Nutritional parameters, in particular prealbumin levels and lymphocyte subpopulations (CD4+, CD8+, CD16+/56+, and CD69 cells) were evaluated before and after the nutrition protocols. Groups were compared in terms of postoperative complications and duration of hospital stay. RESULTS: Of the 42 patients who completed the study, 16 received immunonutrition, 13 received normal nutrition and 13 received standard enteral nutrition. prealbumin values were low in every group, but this parameter was improved after the nutritional protocol only in the immunonutrition group (13.64 +/- 8.83 vs 15.98 +/- 8.66, P = 0.037). Groups were similar in terms of CD4+, CD16+/56, and CD69+ prior to the nutritional protocol; whereas CD8+ was higher in the standard nutrition group compared to the immunonutrition group. After nutritional protocols, none of the groups had an increase in their lymphocyte subpopulations. Also, groups did not differ in terms of postoperative complications and postoperative durations of hospital stay. CONCLUSION: Preoperative immunonutrition provided a significant increase in prealbumin levels, while it did not significantly alter T lymphocyte subpopulation counts, the rate of postoperative complications and the duration of hospital stay. (C) 2009 The WJG Press and Baishideng. All rights reserved.
Keywords: Malnutrition; Gastrointestinal tumours; Immunonutrition; Prealbumin; Lymphocyte subpopulations; IMMUNOENHANCED ENTERAL NUTRITION; NECK-CANCER PATIENTS; POSTOPERATIVE IMMUNE; PERIOPERATIVE IMMUNONUTRITION; GASTROINTESTINAL CANCER; COLORECTAL-CANCER; SURGICAL-PATIENTS; CLINICAL-TRIAL; HOST RESPONSE; FATTY-ACID